“I am at last vanquished by sickness”: The Narrative of Illness and Disability in Mary Darby Robinson’s Letters - Valentina Pramaggiore (Lea)
This essay will analyse how Mary Robinson recounted her disability and illness in her last letters to her friends. The investigation will explore how she perceived herself as a woman, a mother, a professional writer and a patient in distress, using her pen to construct her multilayered identity. At the same time, it will delve into the relationship between the body and the mind, and how the act of writing in her last months has served the social and therapeutic purpose of enabling a physically fragile subject to make her voice and anguish heard.